Professional and religious education: the Jesuit experience in the colonial Rio Grande (Research, Society and Development, 2018)
The Jesuit experience in Brazil presents several nuances and narratives that describe the relationship between the Jesuit and the Indian, with the colonist and the actions resulting from this contact, all reflecting a metropolitan policy and its adaptations in the Colony. The main agent of this policy was the Jesuit, ally of the Crown and representative of the Church. The Jesuit went through a meticulous professional preparation in the Colleges before the missionary experience that produced a true manager, allying the spiritual and material necessity in the same being. This paper presents two roles - religious and artisan - played by the Jesuits to achieve the objective of catechization. For the development of the research, references are used that discuss the presence of the Jesuits in Brazil both observing the spiritual purpose, as well as the importance of the manual works for the approximation and fixation of the indigenous populations in the missions. It is understood that all preparation prior to the colonial experience can be framed in the concept of professional education, since the missionary was trained during his formation to carry out the work with the natives. Documentary sources produced by the Jesuits are presented on their experience and analyzes produced by local scholars. The study space is the Rio Grande colonial and the narratives resulting from the experience in this locality, therefore the objective of this work is to contribute to the expansion of the understanding of the History of Education in Rio Grande. The results are still incipient, since the research is new and is still in the step of mapping more specific data.